2012
DOI: 10.1371/journal.pone.0039046
|View full text |Cite
|
Sign up to set email alerts
|

Long Distance Movements and Disjunct Spatial Use of Harbor Seals (Phoca vitulina) in the Inland Waters of the Pacific Northwest

Abstract: BackgroundWorldwide, adult harbor seals (Phoca vitulina) typically limit their movements and activity to <50 km from their primary haul-out site. As a result, the ecological impact of harbor seals is viewed as limited to relatively small spatial scales. Harbor seals in the Pacific Northwest are believed to remain <30 km from their primary haul-out site, one of several contributing factors to the current stock designation. However, movement patterns within the region are not well understood because previous stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
50
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 48 publications
(78 reference statements)
4
50
0
Order By: Relevance
“…Previous studies on harbour seals movement patterns indicate that this species is relatively sedentary through out the year, although seasonal shifts between favoured sites is common and in some areas the seals make offshore trips in the vicinity of the main haul-out sites to distances between 20 and 30 km (Thompson & Miller 1990, Thompson et al 1991, Thompson et al 1998b, Vincent et al 2010, Sharples et al 2012). However, longdistance movements have also been recorded in some areas, linked mainly to seasonal migrations to avoid ice or dispersal by immature animals (Lesage et al 2004, Peterson et al 2012, Sharples et al 2012 Table 5. Phoca vitulina.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies on harbour seals movement patterns indicate that this species is relatively sedentary through out the year, although seasonal shifts between favoured sites is common and in some areas the seals make offshore trips in the vicinity of the main haul-out sites to distances between 20 and 30 km (Thompson & Miller 1990, Thompson et al 1991, Thompson et al 1998b, Vincent et al 2010, Sharples et al 2012). However, longdistance movements have also been recorded in some areas, linked mainly to seasonal migrations to avoid ice or dispersal by immature animals (Lesage et al 2004, Peterson et al 2012, Sharples et al 2012 Table 5. Phoca vitulina.…”
Section: Discussionmentioning
confidence: 99%
“…Age, size and sex have also been shown to influence movement patterns of harbour seals (Thompson et al 1998b, Peterson et al 2012. Thompson et al (1998b) reported that sex and body size were correlated with trip duration in harbour seals in Moray Firth (Scotland) and that males had larger foraging ranges than females.…”
Section: Discussionmentioning
confidence: 99%
“…Although harbor seals may range widely during the post-breeding season (Lowry et al, 2001;Peterson et al, 2012;Womble and Gende, 2013), they typically exhibit a high degree of fidelity to pupping areas during the breeding season (Blundell et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Similar trends in harbor seal populations occurred in the Strait of Georgia during the same period (DFO 2010). Harbor seals feed predominantly on Clupeidae (herring) and Gadidae (cod and hake), but also feed opportunistically (Thomas et al 2011) from just a few to over 100 km from their (capture) haul-outs (Peterson et al 2012). Steelhead trout were not identified as prey in a fairly extensive year-round analysis of harbor seal diet around the San Juan Archipelago , Bromaghin et al 2013.…”
Section: Introductionmentioning
confidence: 99%